2019
DOI: 10.3389/fimmu.2019.02990
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Modification of CD8+ T Cells to Express EGFR: Potential Application for Adoptive T Cell Therapies

Abstract: Adoptive immunotherapy with ex vivo-expanded tumor-infiltrating lymphocytes (TILs) has achieved objective clinical responses in a significant number of patients with cancer. The failure of many patients to develop long-term tumor control may be, in part, due to exhaustion of transferred T cells in the presence of a hostile tumor microenvironment. In several tumor types, growth and survival of carcinoma cells appear to be sustained by a network of receptors/ligands of the ErbB family. We speculated that if tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…Recent one study indicated the EGF can be efficiently produced in MC-38 cells and EGF could activate the ERK pathway [15,16], thus we next explored whether MC-38-derived EGF contributed to the overexpression of CCL3 through ERK pathway. Interestingly, the activation of ERK1/2 was prevented in BMMs cultured in CM after treatment with EGF neutralizing antibody (Figure 5A,B).…”
Section: Activation Of Egf/erk/creb Pathway Up-regulates the Expression Of Ccl3 In Bmms During Osteoclastogenic Inductionmentioning
confidence: 99%
“…Recent one study indicated the EGF can be efficiently produced in MC-38 cells and EGF could activate the ERK pathway [15,16], thus we next explored whether MC-38-derived EGF contributed to the overexpression of CCL3 through ERK pathway. Interestingly, the activation of ERK1/2 was prevented in BMMs cultured in CM after treatment with EGF neutralizing antibody (Figure 5A,B).…”
Section: Activation Of Egf/erk/creb Pathway Up-regulates the Expression Of Ccl3 In Bmms During Osteoclastogenic Inductionmentioning
confidence: 99%
“…However, in the present study, AXL was strong and positively correlated to CD8+ T cell from Figure 12(a). CD8+ T cells expressing EGFR could benefit from EGFR ligands produced by the tumor [23]. EGFR is beneficial to CD8+ T cells in bladder cancer.…”
Section: Biomed Research Internationalmentioning
confidence: 99%
“…From further exploration of the unannotated cluster, we found that the cluster was dominated by ribosomal signatures, explaining the inclusion of significant correlations with ribosome-related pathways in our inference (FigS5). More interestingly however, we also uncovered pathways that have been reported to influence CD8+ T cell behavior in other contexts, such as the ROBO receptors and ERBB2 signaling pathways [26][27]. These pathways largely underwent substantial changes in gene expression early on in the pseudotime trajectory, although a portion of the ROBO receptor pathway shifted later on (Fig4F).…”
Section: Tips Analysis Of Complex Progression Trajectoriesmentioning
confidence: 68%